Learn to conserve: The effects of in-school energy education on at-home electricity consumption. (July 2018) - Gill, Carrie; Lang, Corey
Abstract: Environmental education for school students, including lessons on recycling, water conservation, and energy reduction, is a popular measure aimed at increasing environmental knowledge, promoting environmental attitudes, and increasing pro-environmental behaviors. Despite the prevalence of such education, there is little empirical evidence to support the efficacy of these programs on tangible outcomes outside of school. This paper contributes an empirical analysis of a series of energy lessons in the United States. Using a differences-in-differences approach with a rich panel data set, we find evidence for short-term reductions on the order of eight percent in electricity use the day of a lesson regarding energy conservation via reducing phantom electric loads (standby power), with evidence of deferment in electricity use rather than true conservation. We find no effect of lessons on energy pathways or wind energy on the days of the lessons. Despite limited evidence of conservation, our results do indicate a connection between lessons learned in school and measurable behavior at home. Importantly, this research indicates that energy education could be a potentially valuable tool for policy regarding energy conservation and efficiency, though future research is needed to optimize the timing and content of such lessons. Highlights: Case study of energy education's influence on home energy use. Difference-in-difference with matching methodology. Results for one lesson indicate short-term reduction, but also deferment of usage.